Computerized Tomography of the Brain for Elderly Patients Presenting to the Emergency Room with Acute Confusion State in Eastern Nepal (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Acute confusion is a common reason for presentation of elderly patients to the emergency which may be of neurological or non-neurological origin. Computerized tomography (CT) scans are often routinely ordered to investigate the cause. Objective: To determine the usefulness of CT scan brain in confused elderly patients. Methods: A cross-sectional observational study was conducted in emergency room (ER) of B. P. Koirala Institute of Health Sciences over a period of 6 months in 84 patients above the age of 65 years who had CT scan brain done in view of acute confusion. They were reviewed for symptoms, indications of CT scan and presence of focal neurological deficits (FND). Results: Among patients presenting in confusion and with loss of consciousness or limb weakness, CT scan was abnormal in 90% and 92% cases respectively (p 0.05). Out of 84 elderly cases of acute confusion, 52 had FND and the remaining 32 cases were without FND. Among those with FND, 40% and 46% cases had features of ischemic and hemorrhagic stroke respectively. Among the 32 without FND, 66% patients had normal scan and 38% had cerebral atrophy. In patients with Glasgow Coma Scale (GCS) < 9 with FND, 75% had CT scan suggestive of hemorrhagic stroke whereas those with GCS> 13 with FND, 57% and 29% cases had ischemic and hemorrhagic stroke respectively. Conclusion: CT scan brain for confused elderly should be advised for those with focal neurological symptoms and may be suggested in cases of head trauma or alleged history of fall irrespective of GCS and symptomatology.